Exploiting the nonlinear impact dynamics of a single-electron shuttle for highly regular current transport - Moeckel, Michael J.; Southworth, Darren R.; Weig, Eva M.; Marquardt, Florian (My University, 2013)
The nanomechanical single-electron shuttle is a resonant system in which a suspended metallic island oscillates between and impacts at two electrodes. This setup holds promise for one-byone electron transport and the establishment of an absolute current standard. While the charge transported per oscillation by the nanoscale island will be quantized in the Coulomb blockade regime, the frequency of such a shuttle depends sensitively on many parameters, leading to drift and noise. Instead of considering the nonlinearities introduced by the impact events as a nuisance, here we propose to exploit the resulting nonlinear dynamics to realize a highly precise oscillation frequency via synchronization of the shuttle self-oscillations to an external signal.
Keywords: 530